Demand Management Plan For It Services At PPTI Stikom Surabaya Using Standard Service Strategy ITIL V3 - Rochdiansyah, Zhulfiki Arbhi; Sutomo, Erwin; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Development and Application of Information Technology (PPTI) is one part in the Institute of Business and Information Stikom Surabaya (Surabaya Stikom), PPTI an important role in ensuring the course of Systems and Information Technology (STI) for each civitas. Conditions in the PPTI currently do not have users demand patterns of IT services, so thats make PPTI can not understand and know the effect of user demand on services and availability of service capacity to meet that demand. Solutions to these problems, it needs to be planning IT services for needs of Demand Management for IT Services, this process has the objective to anticipate and influence the demand for IT services in PPTI. Plan of Demand Management for IT Service Management, we conducted research with reference to the standard Service Strategy in the framework of the Information Technology Infrastructure Library V.3 (ITIL), especially on Service Strategy which is used as a foundation to support the development process. outcome of the Demand Management for IT Service is create documents Patterns of Business Activity (PBA), User Profile (UP), standards and procedures, and policies Demand Management. The document can function in the process of sorting and managing user requests the service properly and according to the needs, service levels and asset services.